2020
DOI: 10.1523/jneurosci.2569-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Spike Afterpotentials Shape theIn VivoBurst Activity of Principal Cells in Medial Entorhinal Cortex

Abstract: Principal neurons in rodent medial entorhinal cortex (MEC) generate high-frequency bursts during natural behavior. While in vitro studies point to potential mechanisms that could support such burst sequences, it remains unclear whether these mechanisms are effective under in vivo conditions. In this study, we focused on the membrane-potential dynamics immediately following action potentials (APs), as measured in whole-cell recordings from male mice running in virtual corridors (Domnisoru et al., 2013). These a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
(113 reference statements)
2
3
0
Order By: Relevance
“…Different cells, however, differ in their burst behavior. This is consistent with the existence of bursty and nonbursty grid cells (Csordás et al, 2020; Latuske et al, 2015). It remains an open question whether the burstiness of a grid cell differs in novel versus familiar environments.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Different cells, however, differ in their burst behavior. This is consistent with the existence of bursty and nonbursty grid cells (Csordás et al, 2020; Latuske et al, 2015). It remains an open question whether the burstiness of a grid cell differs in novel versus familiar environments.…”
Section: Discussionsupporting
confidence: 88%
“…We found that the heterogeneity between firing fields as well as the firing‐rate redistribution during rate remapping were unrelated to burst firing. The relative frequency of burst events varied from cell to cell, in agreement with previous findings (Csordás et al, 2020; Latuske et al, 2015).…”
Section: Introductionsupporting
confidence: 91%
“…6Ad ). Previous studies of medial entorhinal spiking activity have described cell populations with distinct burst-firing and theta-modulation characteristics 34 36 ; therefore, we asked whether a lack of toroidal structure was due to heterogeneity in the composition of the module. We quantified each cell’s temporal modulation characteristics using the spike train temporal autocorrelogram from the OF session, and by applying clustering to the matrix of autocorrelograms we obtained three cell classes (Fig.…”
Section: Classes Of Grid Cellsmentioning
confidence: 99%
“…Burst timing-dependent plasticity (BTDP) of NMDAR-mediated transmission has been reported in the midbrain (Harnett et al, 2009) and in area CA3 of the hippocampus (Hunt et al, 2013), whereas early work utilized high frequency stimulation of MPP axons to elicit NMDAR-LTP at MPP-GC synapses (O’Connor et al, 1994). BTDP mimics in vivo activity in the entorhinal cortex (Latuske et al, 2015; Ebbesen et al, 2016; Csordas et al, 2020) and dentate gyrus (Pernia-Andrade and Jonas, 2014; Diamantaki et al, 2016; Senzai and Buzsaki, 2017), so we aimed to test whether pre (MPP axons) – post (GC) burst pairing stimulation could trigger homosynaptic LTP of NMDAR-mediated transmission at MPP-GC synapses. To isolate NMDAR-mediated transmission, whole-cell patch-clamp recordings of GCs (holding potential [Vh] = -45 mV) were performed in the presence of 10 µM NBQX and 100 µM picrotoxin to block AMPAR- and GABA A receptor-mediated transmission, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…BTDP of NMDAR-mediated transmission was previously reported in midbrain dopamine neurons (Harnett et al, 2009) and in GC-CA3 synapses (Hunt et al, 2013). In vivo recordings showed that medial entorhinal cortex neurons fire bursts of action potentials (Latuske et al, 2015; Ebbesen et al, 2016; Csordas et al, 2020), and GCs which normally fire sparsely, can generate high frequency bursts of back propagating action potentials (Pernia-Andrade and Jonas, 2014; Diamantaki et al, 2016; Senzai and Buzsaki, 2017). In the present study, we found that pairing pre and postsynaptic burst activity selectively induced homosynaptic NMDAR-LTP at MPP-GC.…”
Section: Discussionmentioning
confidence: 99%